2013
DOI: 10.3109/14647273.2013.778423
|View full text |Cite
|
Sign up to set email alerts
|

The anxiety of infertility: The role of the nurses in the fertility clinic

Abstract: This paper discusses the effects of anxiety and depression on infertile people as they undergo infertility investigations and treatments, and explores what nurses may do to assist them to cope with this anxiety. There is an extensive literature on the psychosocial effects of infertility on couples, women and men separately and their children, but the nursing and midwifery literature lacks an in-depth exploration of the psychological and emotional consequences of infertility for infertile people. The paper conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
(39 reference statements)
0
5
0
1
Order By: Relevance
“…Our interest in conducting this psychometric study arose from the need to understand how this stressful experience may disrupt the individual's major life domains. This paper and the proposed questionnaire have implications for the clinical practice of healthcare professionals, especially nurses, who come into contact with infertile people in clinical settings worldwide, because collecting this information can help them to plan effective counselling interventions to reduce negative affect in couples turning to ART (Allan , Arslan‐Özkan et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Our interest in conducting this psychometric study arose from the need to understand how this stressful experience may disrupt the individual's major life domains. This paper and the proposed questionnaire have implications for the clinical practice of healthcare professionals, especially nurses, who come into contact with infertile people in clinical settings worldwide, because collecting this information can help them to plan effective counselling interventions to reduce negative affect in couples turning to ART (Allan , Arslan‐Özkan et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Calls for nursing research have been made to address this gap to identify the known attributes of spirituality and to review the empirical research, with the focus on qualitative studies in different samples and settings to ascertain potential positive benefits or associations (Weathers et al., ). This idea is reinforced by the need for funding to be made available for nursing research in ART (Allan, ) and concerning spiritual care in particular (Roudsari et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Midwives seem to play an important role to stress management of the infertile couple. Till recently the common practice, when dealing with stress in infertility, involved, clinic-based support groups, as a more traditional approach, individual psychological support, counselling and of course online search for current data [12]. Studies have shown that the midwife is enrolled to support this concept.…”
Section: The Role Of the Midwife In The Emotional Guidance And Stress Management Of The Infertile Couplementioning
confidence: 99%